Impact of pelvic immobilization techniques on the outcomes of primary and secondary closures of classic bladder exstrophy. Issue 4 (August 2019) - Zaman, M.; Kasprenski, M.; Maruf, M.; Benz, K.; Jayman, J.; Friedlander, D.; Di Carlo, H.; Sponseller, P.; Gearhart, J.
Summary: Introduction: A potential determinant of successful bladder closures in patients with classic bladder exstrophy (CBE) is the postoperative pelvic immobilization technique. This study investigates the success rates of primary and secondary bladder closures based on various immobilization techniques from a high-volume exstrophy center. Methods: A prospectively maintained institutional exstrophy-epispadias complex database of 1336 patients was reviewed for patients with CBE who have undergone primary or secondary closures between 1975 and 2018 and subsequently had a known method of pelvic immobilization. Patients were divided into two groups: primary and secondary closures. Associations between closure outcomes and immobilization techniques were determined. Results: A total of 476 patients with primary closures and 101 patients with secondary closures met the inclusion criteria. In total, 343 (72.1%) primary closures were successful. As shown in the table, the success rates of primary closures were highest in patients immobilized with modified Buck's and Bryant's traction (95.0% and 79.3%, respectively) and lowest in those with spica cast (49.6%). A propensity score–adjusted logistic regression (adjusting for osteotomy status, period of closure, location of closure, and closure type) revealed that modified Buck's traction had a 5.60 (95% confidence interval 1.74–23.1, p = 0.008) greater odds of success compared to spica casting during the primary closure. For the secondary closure group, there were 92 (92.1%) successful secondary closures. Success rates were highest in modified Buck's traction (97.3%) and lowest with spica casting (66.7%). Discussion: This study confirms previous findings of better outcomes when patients are immobilized with external fixation and Buck's traction after adjusting for potential confounding factors. Immobilization with modified Buck's or Bryant's traction yielded significantly higher primary closure success rates when compared to spica casting. It is the authors' belief that despite a longer hospital length of stay, external fixation with Buck's traction provides the best chance of a successful closure and, thus, a financially responsible method to care for these children in the postoperative period. Table Primary and secondary successful closures by immobilization type. Table Immobilization technique Total primary closures, n Successful primary closures, n (%) Total secondary closures, n Successful secondary closures, n (%) Bryant's traction 169 134 (79.3) 16 12 (75) Buck's traction with external fixation 100 95 (95.0) 75 73 (97.3) Spica cast 139 69 (49.6) 9 6 (66.7) Mummy wrap 40 23 (57.5) 1 1 (100) Other a 28 22 (78.6) – – a Other immobilization techniques: lower extremity traction (≤4 weeks), internal pins, Velcro pelvic binder, Montgomery straps, Russell traction, Kling dressing and adduction splint for the thighs, and unspecified leg wraps. Conclusions: Success rates for primary closures were highest when using modified Buck's traction with external fixation and lowest for spica casts. Similarly, for secondary closures, the best outcomes were achieved using modified Buck's traction with external fixation and the lowest success rates were associated with spica casts.